The Rheological Properties of Lipid Monolayers Modulate the Incorporation of l-Ascorbic Acid Alkyl Esters - Díaz, Yenisleidy de Las Mercedes Zulueta (Langmuir : the ACS journal of surfaces and colloids, 2016)
In this work, we tested the hypothesis that the incorporation of amphiphilic drugs into lipid membranes may be regulated by their rheological properties. For this purpose, two members of the l-ascorbic acid alkyl esters family (ASCn) were selected, ASC16 and ASC14, which have different rheological properties when organized at the air/water interface. They are lipophilic forms of vitamin C used in topical pharmacological preparations. The effect of the phase state of the host lipid membranes on ASCn incorporation was explored using Langmuir monolayers. Films of pure lipids with known phase states have been selected, showing liquid-expanded, liquid-condensed, and solid phases as well as pure cholesterol films in liquid-ordered state. We also tested ternary and quaternary mixed films that mimic the properties of cholesterol containing membranes and of the stratum corneum. The compressibility and shear properties of those monolayers were assessed in order to define its phase character. We found that the length of the acyl chain of the ASCn compounds induces differential changes in the rheological properties of the host membrane and subtly regulates the kinetics and extent of the penetration process. The capacity for ASCn uptake was found to depend on the phase state of the host film. The increase in surface pressure resultant after amphiphile incorporation appears to be a function of the capacity of the host membrane to incorporate such amphiphile as well as the rheological response of the film. Hence, monolayers that show a solid phase state responded with a larger surface pressure increase to the incorporation of a comparable amount of amphiphile than liquid-expanded ones. The cholesterol-containing films, including the mixture that mimics stratum corneum, allowed a very scarce ASCn uptake independently of the membrane diffusional properties. This suggests an important contribution of Cho on the maintenance of the barrier function of stratum corneum